2015
DOI: 10.1093/ije/dyv096.343
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association Between Body Mass Index and Health-Related Quality of Life.

Abstract: Objective: Health-related quality of life (HRQoL) is an important outcome in individuals with a high risk for cardiovascular diseases. We investigated the association of HRQoL and body mass index (BMI) as an indicator for obesity.Design: Secondary longitudinal analysis of the ORBITAL study, an intervention study which included high-risk cardiovascular primary care patients with hypercholesterolemia and an indication for statin therapy.Methods: HRQoL was determined with the generic Short Form (SF)-12 health sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Previous systematic reviews and meta‐analyses of cross‐sectional studies have similarly demonstrated a strong dose‐responsive inverse relationship between weight and physical HRQOL in both adults and children . Secondary analyses of longitudinal intervention studies further show that weight gain is associated with reduced physical HRQOL . The mechanism of this association is unknown.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous systematic reviews and meta‐analyses of cross‐sectional studies have similarly demonstrated a strong dose‐responsive inverse relationship between weight and physical HRQOL in both adults and children . Secondary analyses of longitudinal intervention studies further show that weight gain is associated with reduced physical HRQOL . The mechanism of this association is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…In children, one review showed an inverse relationship between weight and overall mental HRQOL, while three reviews found that only one PedsQL mental subscale was consistently lower at higher weights . Longitudinal intervention studies found weight gain to be variably associated with improved and reduced mental HRQOL. It is possible that weight and mental HRQOL are unrelated or only weakly related, with mental HRQOL only affected at extremes of weight change.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that higher HbA1c was associated with lower HRQOL [12], but other studies showed no association between HbA1c and HRQOL over time [13][14][15]. Inconsistent relationships between BMI and HRQOL over time were found in previous studies [15][16][17]. Hence, further study is needed to provide more evidence on the predictors for HRQOL among type 2 diabetic patients.…”
Section: Introductionmentioning
confidence: 98%